2016
DOI: 10.1080/03079457.2016.1138281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of encapsulated carvacrol on the incidence of necrotic enteritis in broiler chickens

Abstract: There is an urgent need to control necrotic enteritis (NE) caused by Clostridium perfringens in chickens when antibiotics are withdrawn from feed. Carvacrol has strong antimicrobial activity and its delivery to the animal intestine can be significantly enhanced after encapsulation. The present study has investigated the potential of encapsulated carvacrol in controlling NE. In general, micro-encapsulation of carvacrol in an alginate-whey protein matrix showed no adverse effect on its antimicrobial activity tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
0
16
1
Order By: Relevance
“…In the same study, concerning gastrointestinal morphology, histological analysis at slaughter indicated an increase in small-intestinal VH, and the increased expression of mucin mRNA in both large and small intestines. Liu et al (131) found that adding encapsulated carvacrol (250 and 650 mg/kg) appeared to be effective in lessening the severity of necrotic enteritis lesions. Hashemipour et al (132) administered a mixture of carvacrol and thymol in a 1:1 ratio (60, 100 and 200 mg/kg) to broilers, observing an increased antioxidant enzyme activity (superoxide dismutase and glutathione peroxidase) and a retarded lipid oxidation underlined by a decreased level of MDA.…”
Section: Terpenesmentioning
confidence: 99%
“…In the same study, concerning gastrointestinal morphology, histological analysis at slaughter indicated an increase in small-intestinal VH, and the increased expression of mucin mRNA in both large and small intestines. Liu et al (131) found that adding encapsulated carvacrol (250 and 650 mg/kg) appeared to be effective in lessening the severity of necrotic enteritis lesions. Hashemipour et al (132) administered a mixture of carvacrol and thymol in a 1:1 ratio (60, 100 and 200 mg/kg) to broilers, observing an increased antioxidant enzyme activity (superoxide dismutase and glutathione peroxidase) and a retarded lipid oxidation underlined by a decreased level of MDA.…”
Section: Terpenesmentioning
confidence: 99%
“…Therefore, it is expected that the anticoccidial effect of EO will be enhanced if they are specially encapsulated to release active components slowing during passage of the gut thus enable to act on the Eimeria present in duodenum to ceca. Similar strategies with encapsulated EO (EEO) on necrotic enteritis or Salmonella has been reported [9,10].…”
Section: Introductionmentioning
confidence: 62%
“…Therefore, it is expected that the anticoccidial effect of EO will be enhanced if they are technically encapsulated to release active components slowly during passage of the gut, thus enabling action on the Eimeria present in duodenum to ceca. Similar strategies with encapsulated EO (EEO) on necrotic enteritis or Salmonella have been reported [9,10].…”
Section: Introductionmentioning
confidence: 69%